Mechanical Properties of Thermoplastic Variable-Angle Composite Laminations for Conical Shells - Han, Z.Y.; Li, Y.H.; Fu, H.Y. (Проблемы прочности, 2014)
Thermoplastic composite automated fiber placement technology, as one of the extreme manufacturing technologies for large or extra large composite components with complex surface shapes, has been widely used in the field of aerospace vehicles. This paper takes 8 lamination groups with different initial placement angles generated by the conical shell variable angle placement algorithm as research objects. Variable angle placement algorithm for conical shell and finite element model establishment method for thermoplastic composite laminations of variable angle with different initial placement angles are presented. Static, modal and buckling analyses are conducted for each group. The results show that stress-strain relation, modal and buckling strength of variable-angle laminations vary regularly with the initial placement angle.